Mechanically induced cis-to-trans isomerization of carbon–carbon double bonds using atomic force microscopy. Issue 45 (7th November 2016) - Radiom, Milad; Kong, Phally; Maroni, Plinio; Schäfer, Mark; Kilbinger, Andreas F. M.; Borkovec, Michal
Abstract : Single molecule force spectroscopy can be used to induce cis -to- trans isomerization in carbon–carbon double bonds. Abstract : Cis -to- trans isomerization of carbon–carbon double bonds can be induced by the application of mechanical force. Using single molecule force spectroscopy by means of atomic force microscopy (AFM) we pulled polymer molecules which contained cis double bonds in the backbone. In the force versus extension profiles of these polymers, a sudden extension increase is observed which is due to the conversion of shorter cis isomers into longer trans isomers. The added length to the polymer results in relaxation in probed force. We find that the isomerization occurs at forces of 800 ± 60 pN, independent of AFM tip and solid substrate chemistries. Investigation of similar polymers which exclusively contained single bonds in the backbone showed no evidence of a similar transition.